PENGARUH GOOD CORPORATE GOVERNANCE DAN PRUDENT AKUNTANSI TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANFAKTUR 2014-2017 - Basuki Basuki; Indra Gunawan Siregar (COMPETITIVE, 2019)
This study aims to find out empirically how empirical governance factors consist of managerial ownership, institutional ownership, board of commissioners' size and prudent accounting for the increase in firm value. The presence of corporate governance in the recovery of the crisis in Indonesia is absolutely necessary. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2017. The sampling method used was purposive sampling with predetermined criteria based on research variablesThe results of this study indicate that managerial ownership variables, institutional ownership and the size of the board of commissioners do not affect the value of the company. While prudent accounting has a significant negative effect on firm value.